Evolutionary Pattern of High Variation Traits in Subfamily Zygophylloideae (Zygophyllaceae) - Jiancheng Wang; Honglan Yang; Tohir A. Bozorov; Dirk C. Albach; Daoyuan Zhang (Acta Societatis Botanicorum Poloniae, 2020)
Patterns in traits and trait combinations reflect how organisms cope with their environment. Owing to different degrees of variability, the performance of traits varies during adaption to the changing environment. In this study, we focused on a taxon dominant in arid regions – the subfamily Zygophylloideae. We analyzed the evolutionary patterns of functional traits to clarify the impact of trait attributes on niche shifts. The results of phylogenetic signal analysis of traits revealed that quantitative traits, such as plant height, were not evolutionarily conserved. Phylogenetic regression pointed out that there are synergistic changes in environmental factors and in some traits within a phylogenetic context. These traits can meet the requirements of different environments more easily, possibly owing to their high variability. As a result, species in the subfamily Zygophylloideae showed clustering in some phenotypic spaces. Thus, the adaptive evolution of traits reduced niche restrictions of related environmental factors on species. The evolutionary analysis of functional traits in subfamily Zygophylloideae proved that high variability of traits allows fine-tuning according to the related environmental factors during the evolutionary process and promotes niche shifts.